2018
DOI: 10.1111/pops.12525
|View full text |Cite
|
Sign up to set email alerts
|

Applying Moral Foundations Theory to Identify Terrorist Group Motivations

Abstract: Previous research distinguishing terrorist groups has employed categorical schemes that are (1) ideologically broad and ambiguous (e.g., right‐wing versus left‐wing) or (2) focused on single‐issues (e.g., guns, abortion). Broad schemes often fail to clearly distinguish groups’ motivations, and single‐issue schemes provide no coherent theoretical structure for understanding terrorist behavior. To address these limitations, we applied the conceptual framework of moral foundations theory (MFT) to derive a content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The binding motivations of loyalty, authority, and purity appear to underlie religious terrorist groups (Hahn, Tamborini, Novotny, Grall, and Klebig 2018). The PPT-US (Profiles of Perpetrators of Terrorism in the United States) dataset provides detailed information on all known terrorist organizations to have committed a terrorist attack in the United States from 1970-2016, including their philosophy statements (Miller and Smarick, 2012).…”
Section: Moral Certainty/moral Identitymentioning
confidence: 99%
See 2 more Smart Citations
“…The binding motivations of loyalty, authority, and purity appear to underlie religious terrorist groups (Hahn, Tamborini, Novotny, Grall, and Klebig 2018). The PPT-US (Profiles of Perpetrators of Terrorism in the United States) dataset provides detailed information on all known terrorist organizations to have committed a terrorist attack in the United States from 1970-2016, including their philosophy statements (Miller and Smarick, 2012).…”
Section: Moral Certainty/moral Identitymentioning
confidence: 99%
“…The PPT-US (Profiles of Perpetrators of Terrorism in the United States) dataset provides detailed information on all known terrorist organizations to have committed a terrorist attack in the United States from 1970-2016, including their philosophy statements (Miller and Smarick, 2012). Hahn et al (2018) coded the most salient moral foundations depicted in the philosophy statements of these terrorist organizations and found that the binding motivations of loyalty, authority, and purity are the most common among religious terrorist groups. Purification rituals of sacrifice can expel the guilty and unclean, maintaining the purity of the community (Jones, 2008).…”
Section: Moral Certainty/moral Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the bulk of research on inspirational media has examined narratives' ability to evoke a sense of meaningfulness and normatively positive outcomes in audiences, inspiration can also be used as a manipulation tactic. For instance, marketing scholars attempt to leverage inspirational processes for product persuasion (Barry & Gironda, 2018), extremist groups rely on eudaimonic entertainment cues to cover calls for violence (Bouko, Naderer, Rieger, Van Ostaeyen, & Voué, 2021;Frischlich, 2021), and terrorist organizations justify their atrocities with meaning-promising morality (Hahn, Tamborini, Novotny, Grall, & Klebig, 2019). As such, the communication field's idealizations of inspirational media as socially beneficial stands in stark contrast to the use of inspiration and related constructs in explaining outcomes that may be normatively deemed socially detrimental.…”
Section: Introductionmentioning
confidence: 99%
“…This “dark” side of eudaimonic entertainment is also apparent in the context of extremist and terrorist propaganda itself. Content analytical work shows that, during its peak influence, the self-declared “Islamic state” relied heavily on utopic narratives to recruit its foreign fighters (Winter, 2018) and terrorists across the ideological spectrum frame their mission in moral terms (Hahn et al, 2019). Furthermore, radicalization research suggests that the search for significance and meaning in life are crucial factors in individual radicalization processes (Kruglanski, 2009; Kruglanski et al, 2013).…”
mentioning
confidence: 99%